2023
DOI: 10.1002/cam4.5777
|View full text |Cite
|
Sign up to set email alerts
|

AIRE illuminates the feature of medullary thymic epithelial cells in thymic carcinoma

Abstract: Despite the clear distinction between cortical (cTECs) and medullary thymic epithelial cells (mTECs) in physiology, the cell of origin of thymic carcinomas (TCs) and other thymic epithelial tumors remained enigmatic. We addressed this issue by focusing on AIRE, an mTEC‐specific transcriptional regulator that is required for immunological self‐tolerance. We found that a large proportion of TCs expressed AIRE with typical nuclear dot morphology by immunohistochemistry. AIRE expression in TCs was supported by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Indeed, the scRNA-seq data showed that each TET contained varying proportions of neoplastic TECs resembling normal cTECs and mTECs within the tumor, containing a small number of AIRE-expressing cells ( 88 , 89 ). In great contrast, our study combining immunohistochemical analysis for AIRE with published scRNA-seq data demonstrated that most thymic carcinomas express AIRE protein and harbor the molecular characteristics of several subpopulations in mTECs, but not cTECs, suggesting their cell of origin as mTECs ( 92 ). A recent report also demonstrated that a tuft cell-like signature was prevalent in thymic carcinomas ( 93 ).…”
Section: Single-cell Analysis Beyond Mtecscontrasting
confidence: 66%
See 1 more Smart Citation
“…Indeed, the scRNA-seq data showed that each TET contained varying proportions of neoplastic TECs resembling normal cTECs and mTECs within the tumor, containing a small number of AIRE-expressing cells ( 88 , 89 ). In great contrast, our study combining immunohistochemical analysis for AIRE with published scRNA-seq data demonstrated that most thymic carcinomas express AIRE protein and harbor the molecular characteristics of several subpopulations in mTECs, but not cTECs, suggesting their cell of origin as mTECs ( 92 ). A recent report also demonstrated that a tuft cell-like signature was prevalent in thymic carcinomas ( 93 ).…”
Section: Single-cell Analysis Beyond Mtecscontrasting
confidence: 66%
“…Although the role of AIRE and mTECs in the pathogenesis of MG is still elusive, the absence or the insufficiency of AIRE expression from thymoma tissues has been discussed with the development of autoimmunity in thymoma patients in several studies ( 97 100 ). However, our immunohistochemical approach revealed that most type B thymomas, in which paraneoplastic autoimmunity is most frequent, harbored focal but intense AIRE staining in the area showing differentiation to mTECs ( 92 ). Furthermore, we did not see a correlation between the incidence of MG and the expression of AIRE protein in our TET cohort, raising a possibility that some other factors than AIRE might be responsible for the development of MG in thymomas.…”
Section: Single-cell Analysis Beyond Mtecsmentioning
confidence: 94%
“…The most classical and reliable markers for thymic SQCC are KIT and CD5 [10,[25][26][27]45]. The strong correlation between KIT expression and the tuft cell lineage [19,20,29], along with the observation that CD5 expression was relatively confined to the neuroendocrine group [as previously described [7] and confirmed even in adult TECs alone (shown later)], suggested that CD5 expression might be associated with specific transcription factors related to neuroendocrine lineages.…”
Section: Nfatc1 Expression In Thymic Carcinoma and Ionocytes In The A...mentioning
confidence: 71%
“…The histogenesis of thymic epithelial tumors (TETs) has been the subject of extensive research, with insights drawn from normal thymic physiology and the technological tools available at the time [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Immunohistochemical studies have played a pivotal role in this exploration, leading to the widely accepted notion that type B thymomas, particularly the B2 subtype [ 10 ], largely exhibit a phenotype of cortical thymic epithelial cells (cTECs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation